Functional and anatomical brain connectivity in psoriasis patients and healthy controls: a pilot brain imaging study after exposure to mentally induced itch. (19th May 2020) - Najafi, P.; Ben Salem, D.; Carré, J.‐L.; Misery, L.; Dufor, O.
Abstract: Background: Despite the prevalence of psoriasis, the processing of itch in psoriasis and its impact on the central nervous system (CNS) remain unclear. Objective: We studied the influence of psoriasis on the CNS using magnetic resonance imaging techniques (fMRI and DTI, respectively) to investigate whether mentally induced itch can modify the functional connectivity or the white matter microstructure of the brain. Methods: Fourteen patients with chronic psoriasis and 15 healthy controls were recruited. Itch was mentally induced in subjects by videos showing others scratching themselves. Results: The observation of functional connectivity during the viewing the video revealed an interconnected network of brain regions that are more strongly coupled in psoriasis patients than in healthy controls. This network links the cerebellum, the thalami, the anteroposterior cingulum, the inferior parietal lobules, the middle temporal poles and the parahippocampal, hippocampal, lingual and supramarginal gyri. We also found connections with the right precuneus and both left insula and superior temporal gyrus. The DTI analysis showed that chronic itch affects the microstructure of white matter, including the anterior thalamic radiations, the superior and inferior longitudinal fasciculi, the corticospinal tracts, the cingulum, the external capsules, the inferior frontal‐occipital fasciculi and both minor and major forceps. Conclusion: Our results indicate that there could exist a network which is more interconnected in psoriasis patients. Among two building blocks of this network, the subnetwork encoding the perception and control of itch sensation is more affected than the subnetwork representing mentalizing and empathy. With an approach consisting of measuring microstructural changes at a local level in the brain, we also contradict the findings obtained with global measures which stated that chronic psoriasis cannot alter the anatomy of the brain. This confirms that itchy pathophysiological conditions have similar effects on functional and structural connectivity as those observed in chronic pain.